INTERACTION OF THE EURASIAN ECONOMIC UNION AND ITS MEMBER STATES IN THE SPHERE OF AGRICULTURE - Entin, Mark; Galushko, Dmitriy (Economics of Agriculture, 2021)
The aim of the paper is to consider the international experience of delineating spheres of responsibility of national and supranational regulators in the sphere of agriculture on the example of the Eurasian Economic Union. Used philosophical, general scientific and special methods helped to provide an assessment of the process, which shows that, due to the incompleteness of the process of economic integration, the existing institutional structure of the Union cannot be considered as finalized, and therefore the assignment of certain powers to the Unions bodies is situational, which prevents the formulation of final conclusions on the specifics of delimiting the spheres of responsibility of national and supranational regulators and the boundaries of powers of national regulators in the agricultural sector. The authors concluded that Eurasian Economic Commissions powers and competence in the sphere of agriculture should be expanded in order to achieve aims of the integration entity.